Strategi Pemanfaatan Hasil Komoditas Pertanian terhadap Kemandirian Ekonomi Petani di Desa Margaluyu, Pangalengan, Kabupaten Bandung - Dewantari, Ayu Puspita; Mahsa, Fadil Alvaro; Zaky, Ahmad; Abimanyu, Muhammad Dimas; Samudra, Imam; Salsabila, Dinda Aurellia; Mahar, Indana Zulfa; Amalia, Shandyaga Nurti (IAI Nasional Laa Roiba Bogor, 2025)
This research explores agricultural commodity utilization strategies to improve farmer’s economic independence in Margaluyu Village, Pangalengan, Bandung. Despite having the potential to produce superior agricultural commodities such as pumpkins, potatoes, and chicory, farmers face challenges in optimizing these resources to achieve economic independence. This study identified barriers such as limited access to modern agricultural technology, fluctuating market prices, and lack of post-harvest processing facilities. Through descriptive qualitative analysis, the study examined current commodity utilization patterns, socio-economic factors, and provided recommendations to maximize the village's agricultural potential. The research emphasizes the importance of post-harvest innovation and diversification of agricultural products to increase income and support sustainable local economic growth. The findings suggest the importance of establishing local processing industries and encouraging collaboration between the government and private sector to improve community welfare and economic independence.